Treatment Pattern and Outcome of Locally Advanced Rectal Cancer in Resource-Constrained Countries: Experience at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia - Elias Amare Hailu; Edom Seife Woldetsadik; Biruk Legesse Tadesse; Abdi Dandena Dibaba; Girum Tessema Zingeta; Hidagewoin Frew Kelemu; Yonas Alemayehu Zewde; Ruth Shimeles Aytehgeza; Kebede H. Begna (JCO Global Oncology)
PURPOSEManagement of locally advanced rectal cancer (LARC) includes neoadjuvant chemoradiotherapy (NACRT) followed by total mesorectal excision. Recently, total neoadjuvant treatment (TNT) has gained attention. In developing countries, patients with rectal cancer often present at advanced stages. This study assesses treatment patterns and outcomes in LARC at a largest referral center in Ethiopia.MATERIALS AND METHODSA cross-sectional study was conducted on 100 patients with LARC treated at Tikur Anbessa Specialized Hospital from January 2020 to September 2022.RESULTSThe median age at diagnosis was 45.5 years (range, 20-86), with 51% male. Of the patients, 81% had no previous oncologic treatment and 75.3% was discussed in a multidisciplinary tumor board. Up-front surgery was planned for 44.4% of patients, whereas 22.2% and 8.6% were assigned to TNT and NACRT, respectively. Among 81 treatment-naïve patients, 79 were triaged for surgery, but only 47 (59.5%) underwent surgery, achieving an 89.9% R0 resection rate. Of 36 up-front planned surgeries, 35 proceeded as planned, whereas only 12 of 43 (28%) planned after neoadjuvant treatment underwent surgery. Neoadjuvant chemotherapy (NACT) was given to 37% of patients, with 16.7% (5 of 30) undergoing subsequent surgery. Radiotherapy was given to 24.2% of participants, with 56.25% undergoing surgery. Short-course radiotherapy (SCRT) was given to two patients. Only 14.8% completed all planned treatments, with radiation waiting time (median, 10 months) being the main impediment.CONCLUSIONTimely administration of neoadjuvant treatment is not possible in most resource-limited settings. Because of better treatment completion, up-front surgery looks a more viable option than NACT in these situations. Extended waiting time for radiotherapy can be mitigated by opting for alternatives like SCRT in selected patients.